Research gaps in multi-criteria decision making methods for researchers as an areas of interest - Omar, Ibrahim Ayasrah; Faiz, Mohd Turan (Penerbit UMP, 2020)
The increase in multi-criteria decision-making studies is reflecting its importance as an interesting area for research. Even though a high number of revealed studies mainly in last decade, still this field has challenges that require attention from researchers in future studies. Most of multi-criteria decision-making studies either have not considered determining decision maker’s weights or applied subjective methods to derive these weights.In addition, the absence of implementing sensitivity analysis to decision maker's weights is noticed. Furthermore, there is a need to develop new methods that utilizing the web or mobile technologies to deal with complexity and uncertainty adhered to multi-criteria decision-making problems. This paper represents a trial to list current challenges in this field as areas of interest for researchers in future studies